2010
DOI: 10.3233/wor-2010-0986
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic design for dental offices

Abstract: The increasing complexity of the dental office environment influences productivity and workflow for dental clinicians. Advances in technology, and with it the range of products needed to provide services, have led to sprawl in operatory setups and the potential for awkward postures for dental clinicians during the delivery of oral health services. Although ergonomics often addresses the prevention of musculoskeletal disorders for specific populations of workers, concepts of workflow and productivity are integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…The AbS was considered by most of the volunteers as a promoter of a more appropriate posture. This same benefit has already been pictured for the lumbar spine considering the use of a support for the trunk [1].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The AbS was considered by most of the volunteers as a promoter of a more appropriate posture. This same benefit has already been pictured for the lumbar spine considering the use of a support for the trunk [1].…”
Section: Discussionsupporting
confidence: 58%
“…Providing support for the lumbar spine when the trunk is inclined forward to access the oral cavity becomes a challenging issue [1]. Therefore, when considering the effort in trunk flexion, this study aims to determine whether the use of an abdominal support interferes with the dentist's electromyographic activity in terms of the superior trapezius and longissimus thoracic muscles, and the distribution of body weight on a dental stool in order to promote a position closer to the central axis while performing a restorative procedure on a dental dummy ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, an additive effect has been suggested to exist when a saddle seat and magnification lenses are used together. Anecdotally, the majority of the loupes manufacturers advise their clients that they should invest in a fibre‐optic light which is added to the loupes or to a headgear to increase visual acuity . These headlamps can increase the light levels to as much as 4 times the intensity of the traditional overhead dental light.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that dental practitioners spend a mean of 44 hours per week in their practice [25] and they spend about 78 percent of their working time seated [26]. In regards to the dental stool it is recommended to obtain a stool that offers neutral back, neck and shoulder support for optimal posture and possesses an adjustable height and tilt [27,28]. …”
Section: Discussionmentioning
confidence: 99%